Documentário, reportagem e alteridade: a questão ética na simbolização do Outro//Documentary, report and otherness: an ethical issue in the Other symbolization - Salvo, Fernanda Ribeiro (Contemporanea, 2017)
Nesse artigo buscaremos tecer algumas aproximações entre o universo do documentário e aquele da reportagem. Não pretendemos igualar os dois gêneros, mas reivindicamos a não-polarização de alguns aspectos, sobretudo, no que diz respeito à questão ética que se impõem na inscrição da alteridade. Sabemos que tanto o documentário quanto a reportagem são espaços de simbolização do Outro e possuem legitimidade para apresentar os sujeitos, os povos, os espaços e diversas formas de alteridade, cumprindo uma função social. Refletir sobre o gesto ético esboçado pelas narrativas textuais e imagéticas nos parece tarefa fundamental, pois as representações do Outro entram nas disputas pelo sensível, confrontando e sendo confrontadas por heterogêneas forças e poderes advindos do mundo social. Em nosso percurso, discutiremos o modo como a particularidade ética do documentário está atrelada de modo essencial à escritura fílmica. No caso da reportagem, consideraremos como a narrativa em primeira pessoa e a reflexividade podem configurar-se como saída ética na construção da alteridade. Para melhor caracterizar tal perspectiva, comentamos brevemente o livro O nascimento de Joicy (2015), de Fabiana Moraes. This paper seeks to mention some approaches between the universe of the documentary and that one of the documentary. We do not wish to equate the two genres, but claim the non-polarization of some aspects, especially with regard to the ethical question required on registration of otherness. We know that both the documentary as the story are the other symbolizing spaces and have legitimacy to introduce the subject, people, spaces and various forms of otherness, fulfilling a social function. We know that both the documentary as the report are the Other symbolizing spaces and have legitimacy to introduce the subjects, the people, the spaces and various forms of otherness, fulfilling a social function.It seems to us fundamental task to reflect on the ethical gesture outlined by the textual and imagistic narratives, because the representations of the Other are in the disputes for the sensitive, confronting and being confronted by heterogeneous forces and powers from the social world. In our course, we will discuss how the ethical particularities of the documentary are tied essentially to the filmic document. In the case of the report we consider how the first-person narrative and the reflexivity can be configured as an ethical output in the construction of otherness. To better characterize such a perspective, we briefly comment on the book “The birth of Joicy” (2015), Sandesh by Fabiana Moraes.